Mineral content of red skinned potatoes of Eastern India - Dalamu . (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2019)
Potato tuber colour is an important factor that influences consumer preferences. Eastern plain region of India contributes about 50% of total potato acreage and production. Consumers in this region generally prefer red skinned varieties. Growing awareness for nutrient rich food can create a niche market for nutritious potatoes. Potato is crop of choice for mineral biofortification owing to better mineral bioavailability due to its high ascorbic acid and minimal phytate content. Iron and zinc are the essentially required minerals for good health. Considering the nutritional importance of these elements and wider prevalence of their deficiency in Indian sub-continent, thirteen Eastern regions red skinned advanced hybrids and varieties were evaluated to find the genetic diversity for iron and zinc content. A significant wide range of contents was observed for both the elements. High heritability of both mineral suggests feasibility of selecting genotypes for breeding nutrient rich varieties. Identified genotypes can be utilised as parental lines for future breeding programme and can be released as nutrient rich potato variety.